Characteristics of Very High-Power, Short-Duration Radiofrequency Applications - Orbán, Gábor; Salló, Zoltán; Perge, Péter; Ábrahám, Pál; Piros, Katalin; Nagy, Klaudia Vivien; Osztheimer, István; Merkely, Béla; Gellér, László; Szegedi, Nándor (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Pulmonary vein isolation is the cornerstone of rhythm-control therapy for atrial fibrillation (AF). The very high-power, short-duration (vHPSD) radiofrequency (RF) ablation is a novel technology that favors resistive heating while decreasing the role of conductive heating. Our study aimed to evaluate the correlations between contact force (CF), power, impedance drop (ID), and temperature; and to assess their role in lesion formation with the vHPSD technique. Methods: Consecutive patients who underwent initial point-by-point RF catheter ablation for AF were enrolled in the study. The vHPSD ablation was performed applying 90 W for 4 s with an 8 ml/min irrigation rate. Results: Data from 85 patients (median age 65 [59-71] years, 34% female) were collected. The median procedure time, left atrial dwelling time, and fluoroscopy time were 70 (60-90) min, 49 (42-58) min, and 7 (5-11) min, respectively. The median RF time was 312 (237-365) sec. No steam pop nor major complications occurred. A total of 6551 vHPSD RF points were analyzed. The median of CF, maximum temperature, and ID were 24 (17-35) g, 47.6 (45.1-50.4) °C, and 8 (6-10) Ohms, respectively. CF correlated significantly with the maximum temperature (p<0.0001). A CF of 5 grams and above was associated with a significantly higher temperature compared to those lesions with a CF below 5 grams (p<0.0001). Bilateral first-pass isolation rate was 84%. The 6-month AF-recurrence rate was 7%. Conclusion: The maximum temperature and CF significantly correlate with each other during vHPSD applications. A CF greater than or equal to 5 grams leads to better tissue heating and thus might be more likely to result in good lesion formation, although this clinical study was unable to assess actual lesion sizes.